Food and Agriculture Policy 1995 - 1997 : white paper (The Ministry Port of SpainTT, 1995)
Identifies the major resources of the sector. Reports on the performance of the sector against the background of existing policies. Identifies the major sectoral issues and outlines the major policy objectives and strategies to match the issues. Presents an implementation schedule for the 1995 to 1997 period.
DC